1997
DOI: 10.1128/jb.179.3.794-804.1997
|View full text |Cite
|
Sign up to set email alerts
|

Autodisplay: one-component system for efficient surface display and release of soluble recombinant proteins from Escherichia coli

Abstract: The immunoglobulin A protease family of secreted proteins are derived from self-translocating polyprotein precursors which contain C-terminal domains promoting the translocation of the N-terminally attached passenger domains across gram-negative bacterial outer membranes. Computer predictions identified the C-terminal domain of the Escherichia coli adhesin involved in diffuse adherence (AIDA-I) as a member of the autotransporter family. A model of the ␤-barrel structure, proposed to be responsible for outer me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
184
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(190 citation statements)
references
References 49 publications
4
184
0
2
Order By: Relevance
“…The control construct (pLAT83) expressing wild-type Bla in the periplasm was obtained by the same strategy, replacing primer A3 with A2 (5Ј-GATCAGATCT AGATTACCAATGCTTAATCAGTG-3Ј), incorporating the stop codon of the bla gene. Plasmid pJM1013 is a medium-copy-number vector expressing the reporter epitope PEYFK fused to the AIDA-I autotransporter domain under the strong P TK promoter, similar to pJM22 (24). The expression of the AIDA-I fusion proteins was analyzed by the separation of the outer membrane fraction of E. coli by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) or by Western blotting using a rabbit antiserum raised against Bla.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The control construct (pLAT83) expressing wild-type Bla in the periplasm was obtained by the same strategy, replacing primer A3 with A2 (5Ј-GATCAGATCT AGATTACCAATGCTTAATCAGTG-3Ј), incorporating the stop codon of the bla gene. Plasmid pJM1013 is a medium-copy-number vector expressing the reporter epitope PEYFK fused to the AIDA-I autotransporter domain under the strong P TK promoter, similar to pJM22 (24). The expression of the AIDA-I fusion proteins was analyzed by the separation of the outer membrane fraction of E. coli by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) or by Western blotting using a rabbit antiserum raised against Bla.…”
Section: Methodsmentioning
confidence: 99%
“…In these studies, both autotransporter domains were shown to efficiently mediate the export of heterologous passenger proteins, such as the B subunit of cholera toxin (CTB), as well as defined epitopes, to the surfaces of E. coli and Salmonella enterica serovar Typhimurium cells. The amount of the heterologous passenger protein presented on the surface was up to 5% of the total bacterial protein in the AIDA-I system (24), demonstrating the potential of autotransporters for biotechnological applications. The autotransporter domains of the Serratia marcescens serine protease (35) and the Shigella flexneri VirG protein (38) have also been successfully employed for surface display.…”
mentioning
confidence: 97%
“…The seminal work on secretion has also demonstrated the potential biotechnological exploitation of the autotransporter secretion pathway, namely, by displaying heterologous proteins on the bacterial surface (453). The possible applications of this autodisplay system are numerous and include (i) exposure of antigenic determinants for vaccine development (142,267,316), (ii) expression of peptide libraries for epitope mapping or antibody specificity test (258), (iii) display of receptor or ligand for binding assays or purification (499,500), (iv) functional domain analyses of a heterologous protein (59,499,500), and (v) bioconversion by expressing enzymatic activity on the bacterial surface (229,230,276). In conclusion, further understanding of the autotransporter secretion pathway and the functions of the passenger domains will facilitate a richer view of the mechanisms and evolution of bacterial pathogenesis and provide important practical applications for the medical and biotechnological communities.…”
Section: Future Directionsmentioning
confidence: 99%
“…n, 1997). Recently, very promising results have also been obtained with systems based on autotransporter proteins, which are characterized by the fact that all information required to reach the bacterial surface resides in one single peptide chain (Maurer et al, 1997 ;Suzuki et al, 1995). Many of these systems have proven versatile with respect to the size and composition of the passenger sequences that can be displayed.…”
Section: Discussionmentioning
confidence: 95%